2009
DOI: 10.1364/josaa.26.000425
|View full text |Cite
|
Sign up to set email alerts
|

Mass detection on mammograms: influence of signal shape uncertainty on human and model observers

Abstract: We studied the influence of signal variability on human and model observers for detection tasks with realistic simulated masses superimposed on real patient mammographic backgrounds and synthesized mammographic backgrounds (clustered lumpy backgrounds, CLB). Results under the signal-known-exactly (SKE) paradigm were compared with signal-known-statistically (SKS) tasks for which the observers did not have prior knowledge of the shape or size of the signal. Human observers' performance did not vary significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…However. prior work suggests that there is little difference in human observer performance between SKE and SKS tasks [3].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However. prior work suggests that there is little difference in human observer performance between SKE and SKS tasks [3].…”
Section: Resultsmentioning
confidence: 99%
“…Such studies may be used to determine, for example, detection limits under controlled conditions such as threshold size or contrast, without requiring image search. Such an approach can be used to compare detection performances of different breast imaging modalities in radiological studies or virtual clinical trials (VCTs) [3,4]. The principal advantage of a model observer (MO) is the ability to reliably, and tirelessly, undertake evaluations of sets of images without recourse to the variables introduced by using groups of human observers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, for pathologies with multiple lesions, the signal parameters differ for each lesion depending on the stage of the lesion, the background tissue characteristics, etc. Several signal-known-statistically (SKS) experiments (where the signal attributes are known statistically) showed that the uncertainty and variability in signal parameters can significantly influence human performance [15], [41], [42]. This suggests that the SKS MOs may have a great potential to be closer to human observers and they have begun to draw more attention in the last decade.…”
Section: B Existing Numerical Observersmentioning
confidence: 99%
“…In order to represent the routine diagnostic process more realistically, we propose a novel nonlinear numerical observer -PCJO for the detection-localization of multiple parametric signals with random amplitude, orientation, size and location. The only known signal parameter for the PCJO is the signal shape, bearing in mind that Castella [42] reported that uncertainty and variability in signal shape do not influence human performance significantly. The PCJO also involves the perception stage to some extent.…”
Section: B Existing Numerical Observersmentioning
confidence: 99%